Analysis on principle of "integrity of goods" in Imamie jurisprudence and Iranian law Emphasis on rights of consumer - Eghbal Ali mirzaei; ali khaledi (مطالعات تطبیقی فقه و اصول مذاهب)
One of the fundamental rights of consumers in relation to vendors of manufactured goods is the right to cancel a transaction or sue for exhibitory action, i.e. claim damages, in case the merchandise is defective. Therefore, in case the actual merchandise to be sold is not seen in a transaction (Kolli Felzammeh),and the supplied merchandise is proved to be defective, the customer is entitled to a replacement. Moreover, if the defective merchandise or service causes a harm to the consumer because of the said defect, the injured party is entitled to ask for compensation. Such a legal action would of course be contingent upon proof of defect. In the Iranian Civil Law, based on Imamie School, the merchandise is assumed to be in a condition of integrity at the time of the agreement. In case of a conflict, this principle requires the customer to be the claimant and the vendor to be the denier. Accordingly, the customer is required to prove that the merchandise was defective at the time of the agreement and that it belonged to the vendor. In line with contemporaneous situations and advanced legal systems, the Iranian Consumer Rights Protection Act (CRPA) of 2009 intends to restrict the Principle of Integrity of Merchandise. In the relationship between suppliers and Consumer; the contract does not presume the integrity of the merchandise. Rather, the statutory presumption is that the merchandise is defective, and it is the vendor who must prove the contrary, and the integrity of the merchandise.